2004
DOI: 10.1177/089484530403100102
|View full text |Cite
|
Sign up to set email alerts
|

Career Placement Concerns of International Graduate Students: A Qualitative Study

Abstract: This qualitative study investigates the career placement concerns of international graduate students returning to their home countries, heading to other countries, or remaining in the United States after their education. Using a phenomenological framework, structured interviews were conducted with 24 participants (i.e., 18 international students, 1 naturalized status student, 3 faculty members, and 2 career counselors). Assertions that emerged suggested that the students possess diverse career plans influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 6 publications
1
25
1
1
Order By: Relevance
“…This is not surprising, as recent research indicated that international students' primary concerns are job search and placement (Shen & Herr, 2004;Spencer-Rodgers, 2000). The international students in this study paired the prospect of working in Canada with the appeal of the comparatively high standard of living here, which included relative stability and safety.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is not surprising, as recent research indicated that international students' primary concerns are job search and placement (Shen & Herr, 2004;Spencer-Rodgers, 2000). The international students in this study paired the prospect of working in Canada with the appeal of the comparatively high standard of living here, which included relative stability and safety.…”
Section: Discussionmentioning
confidence: 82%
“…In the third phase, new career planning issues may emerge when students approach the end of their educational programs. For example, when international students intend to return home, they may seek assistance with career services such as job searching and learning ways to transfer their educational experiences to their home countries (Shen & Herr, 2004;Spencer-Rodgers, 2000). In Canada, international students can expand their career plans by applying for a postgraduation work permit to enhance their qualifications for permanent immigration under the Canadian Experience Class (CIC, 2008).…”
Section: Career Development and International Studentsmentioning
confidence: 99%
“…Again, career services personnel could educate students in their 1st and 2nd years of study about the importance of networking, volunteerism, job search skills, and opportunities for pregraduation work experience or internships. Previous research shows that relevant work experience, in the form of internships or teaching assistantships while in school, enhances students' foundation of experience for pursuing employment after graduation (Shen & Herr, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, approximately 30% of international student graduates change their immigration status to gain additional employment experience (Centre for Educational Research and Innovation, 2011). As students consider their options for employment, career counseling might be helpful in reviewing personal, cultural, and systemic influences on their decision (Arthur, 2007;Shen & Herr, 2004).…”
mentioning
confidence: 99%